Electrical and Optical Properties of the Hybrid TiO\(_2\) Nanocrystals - MEH-PPV Thin Films - Chi, Le Ha (Communications in Physics, 2009)
Recently, the conjugated polymer – inorganic nanocomposites have been increasingly studied because of their enhanced optical and electronic properties as well as their potential application in developing optoelectronic devices. In this study nanocomposite materials thin films based on poly [2-methoxy-5-(2’-ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) and nanocrystalline TiO\(_2\) (nc-TiO\(_2\)) have been fabricated. The photoluminescence (PL) spectra of pure MEH-PPV and nanohybrid films have shown that the excitation at a 377 nm wavelength leads to the strongly enhanced performance in photoluminescent intensity due to the compositions of TiO\(_2\) component. Current-voltage (I-V) characteristics of multi-layer device Al//MEH-PPV:nc-TiO\(_2\)//PEDOT: PSS//ITO//glass were investigated. The results show that the hybrid MEH-PPV:nc-TiO\(_2\) materials with high concentrations of TiO\(_2\) (>25%) can be expected to be a good candidate for photovoltaic solar cell applications whereas those with lower concentrations of TiO\(_2\) are more suitable for organic light-emitting diodes (OLEDs).